Evidence of Spin Canting, Metamagnetism, Negative Coercivity and Slow Relaxation in a Two‐Dimensional Network of Mn6 Cages. Issue 3 (8th September 2017) - Dendrinou‐Samara, Catherine; Walsh, James P. S.; Muryn, Christopher A.; Collison, David; Winpenny, Richard E. P.; Tuna, Floriana
Abstract : The synthesis, crystal structure and magnetic studies are reported for a two‐dimensional network of mixed‐valent Mn6 cages. The compound contains three different bridging ligands: pivalate, phenylphosphonate and partially deprotonated triethanolamine. The result of using three bridging ligands is a complex structure involving a Mn III 2 Mn II 4 edge‐sharing bitetrahedron that interlinks, forming a layered structure. Weak intercage interactions lead to a remarkably complicated magnetic behaviour, with a phase transition at 2.1 K leading to a canted antiferromagnetic state. Abstract : A 2D network of covalently linked Mn2 III Mn4 II entities with two different orientations of their Jahn–Teller axes and complex magnetic behaviour, displaying simultaneously weak ferromagnetism, spin canting, slow magnetic relaxation, metamagnetic behaviour and an unusual reversed hysteresis.